The cost, availability, cultivars, and quality of fruit and vegetables at farmers' markets and three other retail streams in Canberra, ACT, Australia. Issue 5 (3rd September 2019) - O'Kane, Gabrielle Maria; Richardson, Alice; D'Almeida, Michelle; Wei, Hans
ABSTRACT: In Australia, many people fail to meet the recommended intake of fruit and vegetables for good health, frequently citing price, limited availability, and poor quality as barriers to eating more of these core foods. The purpose of the present study was to compare key attributes of fruit and vegetables between farmers' markets and three other retail streams. The four attributes compared were price; availability of types of fruit and vegetables; number of cultivars for each type of fruit and vegetable; and quality based on visual appearance. Prices and quality of individual items at farmers' markets compared satisfactorily with other retail streams, as did cultivar variety for some fruit, but not availability of types of fruit and vegetables. Further research is needed to determine whether contextual features of farmers' markets and alternative assessments of quality, such as taste and freshness, affect consumers' fruit, and vegetable consumption.